2023
DOI: 10.1038/s41598-023-36161-w
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenesis-associated genetic determinants as predictors of thromboembolism and prognosis in cervical cancer

Abstract: Venous thromboembolism (VTE) is a leading cause of death among cancer patients. Khorana score (KS) is the most studied tool to predict cancer-related VTE, however, it exerts poor sensitivity. Several single-nucleotide polymorphisms (SNPs) have been associated with VTE risk in the general population, but whether they are predictors of cancer-related VTE is a matter of discussion. Compared to other solid tumours, little is known about VTE in the setting of cervical cancer (CC) and whether thrombogenesis-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“… 20 However, in recent years, studies have found that the incidence of postoperative DVT is increased in cervical cancer patients, which will seriously affect the prognosis of patients. 21 , 22 Therefore, active intervention and prevention are particularly important for the therapy of patients. Our study retrospectively analyzed the clinical data of patients with cervical cancer, summarized the risk factors of postoperative DVT, and aimed to provide a scientific basis and targeted measures for its early diagnosis, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 20 However, in recent years, studies have found that the incidence of postoperative DVT is increased in cervical cancer patients, which will seriously affect the prognosis of patients. 21 , 22 Therefore, active intervention and prevention are particularly important for the therapy of patients. Our study retrospectively analyzed the clinical data of patients with cervical cancer, summarized the risk factors of postoperative DVT, and aimed to provide a scientific basis and targeted measures for its early diagnosis, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TiC-LYMPHO, a modified TiC-Onco score, was proposed in lymphoma settings [82]. Neto et al (2023) reported PROCR rs10747514 and RGS7 rs2502448 as valuable prognostic biomarkers regardless of VTE and significantly associated with the VTE risk in cervical cancer [95].…”
Section: Genetic-based Risk Assessment Scoresmentioning
confidence: 99%